Helicobacter pylori Antibiotic Resistance: Trends Over Time - Raymond G Lahaie; Christiane Gaudreau (Canadian Journal of Gastroenterology)
Resistance to antibiotics can be a major problem in the treatment of bacterial infections. As the use of antibiotics increases, bacterial resistance to these agents is rising and in many cases is responsible for the failure of treatment regimens. Although the treatment of Helicobacter pylori infection requires the use of more than one antibiotic to obtain adequate eradication rates, the efficacy of the currently used antibiotic combinations has been shown to be decreased by resistance to one of the antibiotics. The use of antibiotics in regimens for the treatment of H pylori is increasing in many countries, including Canada. This increase is both in the use of these antibiotics alone for the treatment of nongastrointestinal infections and in their use in association with proton pump inhibitors for the treatment of H pylori infection. In several European and Asian countries, where resistance to antibiotics is being monitored, it has been demonstrated that H pylori resistance to metronidazole and to clarithromycin increased throughout the 1990s. Thus far, the data available in Canada do not show increased resistance to either of these antibiotics. As for other antibiotics used in the treatment of H pylori infection, such as tetracycline and amoxicillin, the rate of resistance to these agents is still very low and does not constitute a significant problem. Because the efficacy of the regimens used in the treatment of H pylori infection is compromised by resistance to the antibiotics used, it is important that H pylori resistance rates in Canada and throughout the world continue to be monitored. Only with such reliable data can the most optimal regimens be recommended.